Temporal trends of post-contrast acute kidney injury in patients with intravenous administration of iodinated contrast medium - Xi Wu; Ping Yan; Shao-Bin Duan; Xiao-Qin Luo; Ning-Ya Zhang; Ying-Hao Deng (Renal Failure, 2023)
Little is known about whether preventative practices for post-contrast acute kidney injury (PC-AKI) recommended in guidelines have been adopted in clinical practice and translated into a lower incidence of PC-AKI. The aim of this study was to examine the yearly trends in the incidence of PC-AKI, and comorbidities and care practices associated with PC-AKI in hospitalized patients who received intravenous administration of iodinated contrast medium (ICM). Adult patients receiving intravenous ICM at the Second Xiangya Hospital of Central South University in China between 2015 and 2021 were included. Temporal trends in the incidence and risk factors for PC-AKI were evaluated using logistic regression analyses with adjustments for relevant variables. The incidence of PC-AKI has declined significantly from 5.3% in 2015 to 4.1% in 2021 (p < 0.001). This decreasing trend persisted after extensive multivariable adjustments. Of the comorbidities associated with PC-AKI, the proportion of patients with congestive heart failure or hypertension increased, while the proportion of patients older than 75 years, or with an estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m2, diabetic nephropathy, or renal stone disease decreased. Among the care practices associated with PC-AKI, the proportion of patients using nephrotoxic drugs decreased, whereas the proportion of patients receiving intravenous fluids > 1000 mL on the day of ICM administration or using iso-osmolar ICM increased. In conclusion, a declining trend in PC-AKI incidence was observed in patients receiving intravenous ICM between 2015 and 2021, which may be related to increased awareness and efforts to prevent PC-AKI.